1999
DOI: 10.1115/1.482785
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cycle Fatigue of TiNi Shape Memory Alloy and Formulation of Fatigue Life

Abstract: The low-cycle fatigue of a TiNi shape memory alloy was investigated by the rotating-bending fatigue tests in air, in water and in silicone oil. (1) The influence of corrosion fatigue in water does not appear in the region of low-cycle fatigue. (2) The temperature rise measured through an infrared thermograph during the fatigue test in air is four times as large as that measured through a thermocouple. (3) The fatigue life at an elevated temperature in air coincides with the fatigue life at the same elevated te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
69
2
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 14 publications
4
69
2
6
Order By: Relevance
“…[1][2][3] The thermal response of SMAs during cyclic loading has been largely analyzed in the literature, but applications to fatigue are rare or are limited to short time measurement intervals. Temperature variation during the low-cycle fatigue of a nickel-titanium (Ni-Ti) SMA was studied in Tobushi et al [4] The fatigue of a Ni-Ti SMA was also studied, with a focus on the thermal response near stress-induced martensitic transformation, in Alarcon et al [5] The effect of deformation frequency on thermal response was discussed in Yin et al [6] A mechanical dissipation assessment during cyclic loading lasting a few minutes was performed on a copper-based SMA in Bubulinca et al [7] This study is a follow-up of this latter work, with a focus on long-term cyclic tests.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The thermal response of SMAs during cyclic loading has been largely analyzed in the literature, but applications to fatigue are rare or are limited to short time measurement intervals. Temperature variation during the low-cycle fatigue of a nickel-titanium (Ni-Ti) SMA was studied in Tobushi et al [4] The fatigue of a Ni-Ti SMA was also studied, with a focus on the thermal response near stress-induced martensitic transformation, in Alarcon et al [5] The effect of deformation frequency on thermal response was discussed in Yin et al [6] A mechanical dissipation assessment during cyclic loading lasting a few minutes was performed on a copper-based SMA in Bubulinca et al [7] This study is a follow-up of this latter work, with a focus on long-term cyclic tests.…”
Section: Introductionmentioning
confidence: 99%
“…As evidenced by Figure 3, Tobushi et al [11][12][13][14] have contributed significantly to the study of NiTi rotating-bending fatigue for a limited to 0.5-2.5%. These materials engineering studies utilized NiTi wire of slightly larger diameter (0.75 mm), and systematically varied temperature, strain amplitude, environmental fluid, and rotational speed (100 -1000 rpm).…”
Section: Resultsmentioning
confidence: 99%
“…This shortcoming is due chiefly to the distinct approaches to research adopted by these two fields. Materials engineering studies such as those reported by Tobushi et al [11][12][13][14] relate the cycles to failure N f of pseudoelastic NiTi as a function of systematically varied and normalized quantities such as strain amplitude and relative temperature. In such studies, experiments are conducted on model NiTi specimens-smooth wires for which the cross-sectional diameter and the strain amplitude are constant over the length of the wire-but do not consider the range of strain amplitudes consistent with endodontic applications.…”
Section: Introductionmentioning
confidence: 99%
“…That is one reason why BRF has been recognised by various researchers as one important type of fatigue loading. Tobushi et al [12][13][14][15][16] and Miyazaki et al [17,18] have established BRF testing as one standard test to investigate the fatigue behaviour of pseudoelastic shape memory wires. It is interesting to note that the results of BRF experiments have even been utilized in order to assess the fatigue characteristics of vascular stents and orthodontic arch wires [19].…”
Section: Introductionmentioning
confidence: 99%